Sistem pembinaan Akhlaq dalam Tasawuf: Takhally, Tahally, dan Tajally - Fajrin, Nur Cholisa; Fauziah, Fadhillah Salma; Sayunir, Akira Casillas Savero; Faisol, Faisol (Maliki Interdisciplinary Journal, 2024)
This journal explores the moral development system in Sufism through the concepts of takhally, tahally, and tajally. This research aims to analyze how these concepts contribute to improving individual spiritual quality. The research method used is a qualitative approach using literature reviews and analysis of relevant sources. Research findings reveal that the moral development system in Sufism through takhally (self-purification), tahally (self-discipline), and tajally (self-transcendence) plays an important role in forming good qualities and spiritual growth. Further discussion explains the implications of this system in promoting ethical behavior and inner transformation. This research contributes to the understanding of Sufism teachings and provides insight for individuals who wish to develop noble character through Sufism principles.